Performance of two bone substitutes of novel cotton-like β-TCP/PDLGA and granular β-TCP on bone regeneration in the femoral bone defect of the Beagle dogs - Okada, Yasuaki (Bone Rep, 2020)
This study aimed to clarify whether novel cotton-like composite made of β-tricalcium phosphate (β-TCP) and poly(Dl-lactide-co-glycolide) (PDLGA) has a different effect on in vivo bone regeneration after bone defect than that of granular β-TCP. Five male Beagle dogs served as subjects. Cortical and medullary bone defect as non-through holes were made at the diaphysis of the bilateral femurs. One side was implanted with β-TCP/PDLGA (β-TCP/PDLGA group) and the other side was implanted with granular β-TCP (β-TCP group). At 4 weeks after implantation, we found no significant differences in the percentages of newly formed bone area and fibrous tissue area in the bone defect between the two groups. The β-TCP/PDLGA group showed more uniform filling on the surface and earlier disappearance of the material in the medullary region, and there were fewer inflammatory cells and osteoclasts in the bone defect in the β-TCP/PDLGA group. In conclusion, β-TCP/PDLGA performs better at filling the bone defect uniformly and disappears earlier at the cortical and medullary regions while causing less inflammation and bone resorption. Although bone formation activity of the β-TCP/PDLGA group in the cortical region was lower, the newly formed bone volume in bone defect of the β-TCP/PDLGA group was equal to that of the β-TCP group.